Heterologous production of the adhesin LIC13411 from pathogenic Leptospira facilitates binding of non-pathogenic Leptospira in vitro and in vivo - Surdel, Matthew C.; Hahn, Beth L.; Anderson, Phillip N.; Coburn, Jenifer (Frontiers in Cellular and Infection Microbiology, 2022)
Leptospirosis is an important cause of morbidity and mortality worldwide. Disease severity ranges from asymptomatic colonization to widespread hemorrhage and multiorgan dysfunction. The causative agents, Leptospira spp., are zoonotic Gram-negative spirochetes. One important step in pathogenesis is binding of bacterial adhesins to host components. Previously our laboratory identified two L. interrogans candidate adhesins, LIC11574 and LIC13411, that bind to VE-cadherin in vitro. In the current study, we demonstrate the ability of two strains of pathogenic L. interrogans to disrupt the localization of VE-cadherin, a protein important to maintaining inter-endothelial junctions. Purified MBP-LIC11574 and MBP-LIC13411 bind human dermal microvascular endothelial cells in a pattern reminiscent of VE-cadherin, but do not disrupt VE-cadherin localization. Genes encoding the candidate adhesins from pathogenic Leptospira were cloned in an overexpression vector and introduced into non-pathogenic L. biflexa, creating gain-of-function strains producing LIC11574 or LIC13411. Protein production and localization to the outer membrane were confirmed by Triton X-114 fractionation. Although these strains do not disrupt VE-cadherin localization, production of LIC13411 increases binding of non-pathogenic Leptospira to human endothelial cells and specifically to VE-cadherin. In a short-term murine model of infection, LIC13411 production led to increased burdens of the non-pathogen in the lung, liver, kidney, and bladder. These data confirm the role of LIC13411 as an adhesin in Leptospira spp. and implicate it in dissemination to multiple organs. Importantly, anti-adhesin therapy has been shown to have many benefits over classical antibiotics. Taken together, this work provides novel insight into the pathogenesis of Leptospira spp. and identifies LIC13411 as a potential prophylactic and therapeutic target.